Planning Strategy of Operation Business and Maintenance by Analytical Hierarchy Process and Strength, Weakness, Opportunity, and Threat Integration for Energy Sustainability - Suriyanti, Suriyanti; Firman, Ahmad; Nurlina, Nurlina; Ilyas, Gunawan Bata; Putra, Aditya Halim Perdana Kusuma (International Journal of Energy Economics and Policy, 2020)
This study integrates analytical hierarchy process (AHP) and strength, weakness, opportunity, and threat (SWOT) in strategic planning or strategy formulation to demonstrate the qualitative and quantitative integration of techniques between SWOT and AHP in developing business strategies in operation and maintenance (O&M) of power plants. Apart from that, it is to evaluate essential factors in strategic planning and to utilize them in developing effective strategies for the O&M of power plants in the CEPA. Ltd. There are two stages of testing in this study, namely the first stage is data collection and SWOT and TOWS strength analysis. The second stage is the integration of SWOT and AHP. The study was conducted at CEPA. Ltd. as a private company operating in the power generation sector with a research period in the mid to end of 2019. Result ot this study shown Some elements of the strategy that can be done (1). The contract of cooperation with the industry parts supplier, (2). Cooperation contracts can be pursued, one of which is by re-construction of a structured and timely payment process (3). Optimizing company value can be achieved by optimizing CSR (4). Website optimization is a digital-based promotion tool (5). Support in terms of resource development can be completed through training, for example, Basic Welder Scaffolder and Basic Mechanical (6). Any transactions process in foreign currencies to avoid fluctuating exchange rates at the time of purchase or payment. Keywords: Strength, Weakness, Opportunity, and Threat, Analytical Hierarchy Process, Business Operation Management JEL Classifications: C44, D02, L00, L60 DOI: https://doi.org/10.32479/ijeep.9267